An In‐House Prevocational Training Program for Newly Discharged Psychiatric Inpatients: Exploring Its Employment Outcomes and the Predictive Factors. (16th March 2015) - Chuang, Wen‐Fang; Hwang, Eric; Lee, Hui‐Ling; Wu, Shang‐Liang
Abstract Individuals with severe mental disorders continue to experience low employment rates. Occupational therapists play an important role in helping these individuals develop the skills and obtain the supports necessary for productive living. This retrospective cohort study aimed to explore employment outcomes and identify factors predictive of the outcomes of an in‐house prevocational training program designed for newly discharged psychiatric inpatients. Data retrieved from the files of 58 participants including demographics, diagnostic history, physical fitness, functional assessment results, the use of vocational counselling service and employment status were analyzed. The overall employment rates among the participants were high (67.2–79.3%) within the 6 months following the prevocational training program. No significant differences were found in the employment rates across the 1, 3 and 6‐month time periods post‐training. Vocational counselling service post‐training and hand function were two factors predictive of participants' employment outcomes. Occupational therapists should attend to the clients' need for continuous vocational support and carefully identify the personal, functional and environmental factors contributing to successful employment. Caution in interpreting the results is warranted because of the lack of control and randomization in this retrospective study. Additional longitudinal cohort or experimental studies would add further certainty to the current findings. Copyright © 2015 John Wiley & Sons, Ltd.